Situation Report: Romania, 11 September 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu's Foreign Relations: A Shadow of What They Were / by Patrick Moore Romania and the Nonaligned Movement / by Anneli Maier Another Personnel Shuffle / by Patrick Moore Growing Job Insecurity for the Nomenklatura / by Anneli Maier Rewriting History / by Dan Ionescu Romania's Seventh Day Adventists Another Earthquake / by Patrick Moore